LITERASI MATEMATIS SISWA DALAM MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK SATU VARIABEL DIKAJI DARI SELF-ESTEEM - Shinta, Olivia; Yusmin, Edy; T, Ahmad Yani; Hamdani, Hamdani; Fitriawan, Dona (Jurnal AlphaEuclidEdu, 2023)
In this study aims to determine the ability of mathematical literacy in the matter of equations and inequalities absolute value of one variable studied from high, medium and low self-esteem in students. The method used in this research is descriptive. The subjects in this study were students of class X IPA 6, totaling 33 students. The object to be studied is mathematical literacy in the matter of equations and inequalities of the absolute value of one variable studied from student self-esteem. The techniques used in data collection were questionnaires, mathematical literacy test questions and interviews. Students with low self-esteem cannot fulfill all indicators of mathematical literacy. Students who have moderate self-esteem, are able to understand mathematics based on concepts to describe mathematical problems into various contexts, are sufficiently capable of reasoning logically to solve mathematical problems. However, there are still those who have not been able to communicate it in the form of words or writing to predict and draw conclusions and have not been able to apply or practice based on concepts that have been understood as the basis for solving further mathematical problems. Students who have a high level of self-esteem are able to achieve all existing indicators.